Early thrombin formation capacity in trauma patients and association with venous thromboembolism. Issue 147 (November 2016) - Voils, Stacy A.; Lemon, Stephen J.; Jordan, Janeen; Riley, Paul; Frye, Reginald
Abstract: Incidence of venous thromboembolism (VTE) in adult trauma patients is high despite mechanical and pharmacologic prophylaxis. We hypothesized that thrombin formation capacity as measured by calibrated automated thrombogram (CAT) is increased early in hospitalization and is associated with the development of VTE. Methods: We conducted a prospective study in adult, critically ill trauma patients. Plasma was generated from whole blood samples collected within the first 3 days of hospital admission. CAT was used to determine lag time, thrombin peak, time to thrombin peak, endogenous thrombin potential (ETP), and velocity index in plasma samples from patients, and in control samples of platelet-poor, pooled normal plasma. Results: There were 35 trauma patients and 35 controls included in this pilot analysis. Patients were a mean (SD) age of 45 (19) years, and 23 (66%) were male. The most common mechanism of injury was motor vehicle crash followed by falls, and the median (IQR) injury severity score was 17 (12–27). Three patients (8.6%) had deep vein thrombosis (DVT) confirmed by Doppler ultrasound on median hospital day 7. Compared to control samples, patients had significantly longer lag times (3.1 min vs. 2.7 min, p = 0.02) and significantly higher ETP (1136 nM ∗ min vs. 1019 nM ∗ min, p = 0.007), peak thrombin generation (239 nM vs. 176 nM, p < 0.001), and velocity index (108 nM/min vs. 57 nM/min, p < 0.001) (Fig. 1). There was no difference in the time to peak thrombin generation between the two groups (5.5 min vs. 5.7 min, p = 0.22). In the 3 patients with VTE compared to controls, lag times were shorter and velocity index was higher while ETP and peak thrombin generation were similar. There were no statistically significant differences in thrombin generation parameters in patients with or without VTE, but lag time was numerically shorter, and thrombin peak, time to peak and area-under-the-curve (ETP) were numerically lower in patients with DVT. Conclusions: We observed a thrombin generation profile in critically ill trauma patients consistent with an early hypercoagulable state; however, thrombin generation parameters did not discriminate patients with VTE. Highlights: Trauma is associated with coagulation and increased thrombin generation capacity. CAT was used to assess thrombin generation in traumatic injury. Evidence of hypercoagulable state was observed in trauma patients.